Separator, lithium-ion battery, battery module, battery pack and power-consuming device
By adding ceramic fibers and polymer gel coatings on the isolation film of lithium-ion batteries, the problem of uneven distribution of electrolyte is solved, and the cycle life and energy density of the battery are improved.
Patent Information
- Application Number
- CN202110751942.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-07-02
AI Technical Summary
During the cycle charging and discharging process of lithium-ion batteries, the electrode sheets are squeezed with each other due to expansion of the battery cell, and the electrolyte is extruded, resulting in uneven distribution of the electrolyte, resulting in some electrode sheets being liquid-deficient and infiltrated, which in turn lithium is extruded, affecting the battery. cycling performance and safety.
A barrier film is provided, including a porous substrate, a first coating (inorganic particles and binder), a second coating (ceramic fibers) and a third coating (polymer gel). The isolation film enhances the liquid absorption capacity through the "villi" structure of the ceramic fiber, and absorbs the electrolyte through the microporous structure of the polymer gel, producing a swelling pressure-ret sheet to improve the electrolyte distribution.
It effectively improves the poor infiltration caused by insufficient electrolyte or uneven distribution of the battery cell in the corner area, reduces the risk of local lithium extraction of the battery cell, and improves the cycle life and energy density of the battery.
Smart Images

Figure CN115566361B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to an isolation membrane, a lithium-ion battery, a battery module, a battery pack and an electrical device. Background Art
[0002] The battery separator is an insulating film with a porous structure and is an important component of the battery. It can block the positive and negative poles and prevent the positive and negative poles from short-circuiting inside the battery. The battery separator has nanoscale pores inside, allowing lithium ions and other ions to pass freely during the charging and discharging process, providing a channel for the rapid transmission of lithium ions between the positive and negative electrodes.
[0003] During the charge and discharge cycle, the volume of lithium-ion batteries continues to expand, which is manifested externally as changes in thickness and stress. The expansion of the battery cell will cause the pole pieces to squeeze each other, and the electrolyte will be squeezed out, especially in the corner area of the battery cell. Since the gap in the corner area of the battery cell is different from the stress and non-corner area, it is difficult for the isolation membrane to retain liquid, resulting in uneven distribution of electrolyte in the entire battery cell, causing some pole pieces to lack liquid and insufficient wetting, thereby lithium precipitation. In addition, the lack of electrolyte and insufficient wetting will cause the internal resistance of the battery cell to be high, capacity attenuation, and reduced cycle performance, and may even cause safety issues. Summary of the invention
[0004] In view of the problems existing in the background technology, the present application provides an isolation membrane, a lithium-ion battery, a battery module, a battery pack and an electrical device.
[0005] In a first aspect, the present application provides an isolation membrane, comprising: a porous substrate; a first coating, the first coating is disposed on at least one surface of the porous substrate, the first coating comprises inorganic particles and a binder; a second coating, the second coating is disposed on at least a portion of the surface of the first coating, the second coating comprises ceramic fibers; a third coating, the third coating is disposed on at least a portion of the surface of the second coating, the third coating comprises a polymer gel.
[0006] Compared with the prior art, the isolation membrane provided in the present application includes a first coating layer, a second coating layer disposed on at least a portion of the surface of the first coating layer, and a third coating layer disposed on at least a portion of the surface of the second coating layer in sequence on at least one surface of the porous substrate, wherein the first coating layer includes inorganic particles and a binder, the second coating layer includes ceramic fibers, and the third coating layer includes a polymer gel.
[0007] The isolation membrane provided by the present application has a second coating and a third coating added to the porous substrate and the first coating of inorganic particles. Among them, the ceramic fiber in the second coating has a certain flexibility and elasticity due to its "villi"-like structure, which can enhance the liquid absorption capacity of the isolation membrane; the polymer gel in the third coating has a microporous structure, and after absorbing the electrolyte, it swells and generates a lateral force to press against the pole piece, which can improve the situation of insufficient electrolyte caused by the difficulty of retaining liquid in the isolation membrane. Therefore, the isolation membrane provided by the present application can improve the poor wetting of the battery cell caused by insufficient or uneven distribution of local electrolyte.
[0008] Optionally, the second coating layer is provided in one or more areas, and the plurality of second coating layers are spaced and distributed on at least a portion of the surface of the first coating layer; and / or the third coating layer is provided in one or more areas, and the plurality of third coating layers are spaced and distributed on at least a portion of the surface of the second coating layer. Multiple spaced second coating layers and third coating layers can more effectively solve the problem of insufficient or uneven distribution of electrolyte, while controlling the weight and cost of the battery cell and improving the energy density of the battery.
[0009] Optionally, the ceramic fiber is selected from at least one of alumina ceramic fiber, silicon oxide ceramic fiber, silicon nitride ceramic fiber, barium titanate ceramic fiber, titanium oxide ceramic fiber, and magnesium oxide ceramic fiber. Alumina ceramic fiber or silicon oxide ceramic fiber is cheap and light, and can maximize the energy density of the battery while ensuring that the ceramic fiber has a liquid absorption effect.
[0010] Optionally, the thickness of the second coating is 4 μm to 6 μm; further optionally, the thickness of the second coating is 5 μm to 5.5 μm. If the second coating is too thick, the battery energy density will be low and the battery impedance will increase; if the second coating is too thin, the "villi" structure will have low elasticity and will not have a certain liquid absorption effect.
[0011] Optionally, the polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate, polystyrene, polyacrylonitrile, polymethyl acrylate, polyether and fluorine-containing polymer. The polymer gel layer not only plays a role in retaining liquid, but also has the characteristics of good heat insulation, good corrosion resistance and good thermal stability.
[0012] Optionally, the polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate and polystyrene. Among them, polyimide not only has good mechanical properties and heat resistance, but also has good electrolyte wetting properties, which can enable the isolation membrane to have a high electrolyte retention capacity while maintaining strong structural stability. Polyethylene terephthalate has excellent electrical insulation, good electrical properties, fatigue resistance, friction resistance and dimensional stability. Polystyrene is easy to process and shape, inexpensive, and has good thermal insulation, insulation and corrosion resistance.
[0013] Optionally, the thickness of the third coating is 3 μm to 5 μm, and further optionally, the thickness of the third coating is 4 μm to 4.5 μm. If the third coating is too thick, it will not only reduce the energy density of the battery, but also increase the resistance of the electrolyte passing through the coating, and the electrolyte cannot well infiltrate the entire isolation membrane. If the third coating is too thin, it will affect the liquid retention ability of the gel and fail to achieve a better liquid retention effect.
[0014] Optionally, the particle size of the polymer gel particles in the third coating is 100nm to 1000nm; further optionally, the particle size of the polymer gel particles in the third coating is 300nm to 500nm. If the particle size of the polymer gel particles is too small, the impedance of the isolation membrane will increase, and it will be more difficult for lithium ions to pass through the isolation membrane, and the transmission speed will be reduced. If the particle size of the polymer gel particles is too large, the adsorption capacity of the isolation membrane to the electrolyte will be reduced, affecting the liquid retention effect.
[0015] Optionally, the polymer gel particles in the third coating are solid particles or hollow particles. When the polymer gel particles are hollow particles, the swelling effect of the polymer gel layer after absorbing the electrolyte is more significant, which can more effectively improve the situation of insufficient electrolyte caused by the difficulty of retaining liquid in the isolation membrane.
[0016] Optionally, the inorganic particles in the first coating layer include at least one of the following inorganic particles: silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide and tin oxide.
[0017] Optionally, the binder in the first coating includes at least one of the following adhesives: styrene, acrylate, vinyl acetate, fatty acid vinyl ester, epoxy resin, linear polyester, polyvinylidene fluoride, polystyrene, polysulfide rubber, polyacrylic acid, polyacrylate, polyurethane, polyisobutylene, polyvinyl alcohol, polyimide, polyacrylonitrile, polyethylene oxide, polyvinyl pyrrolidone, styrene-butadiene rubber and gelatin.
[0018] In a second aspect, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the separator is the separator according to the first aspect of the present application.
[0019] Optionally, the lithium-ion battery provided by the present application includes a wound electrode assembly, and the second coating is at least disposed on at least a portion of the surface of the first coating in the corner region of the separator. The corner region is more prone to poor wetting caused by insufficient or uneven distribution of electrolyte. The second coating and at least a portion of the first coating surface disposed in the corner region of the separator can effectively improve the poor wetting of the battery cell caused by insufficient or uneven distribution of electrolyte in the corner region, reduce the risk of local lithium deposition in the battery cell, and increase the cycle life of the battery cell.
[0020] Optionally, multiple second coatings are spaced apart on a portion of the surface of the first coating, and the total area of the multiple second coatings accounts for 88% to 95% of the area of the corner area of the separator. Optionally, the total area of the multiple second coatings accounts for 90% to 92% of the area of the corner area of the separator. When the total area of the second coating accounts for too large a proportion of the area of the separator in the corner area of the battery cell, the resistance of lithium ions passing through the separator will increase, the transmission rate will decrease, the electrolyte will not be able to achieve the best effect of wetting the separator, and the impedance of the entire lithium battery will also increase; when the total area of the second coating accounts for too small a proportion of the area of the separator in the corner area of the battery cell, the ceramic fiber "villi" structure is less, the liquid absorption capacity of the separator in the corner area cannot be significantly improved, and at the same time, the lateral force generated by the swelling of the polymer gel after absorbing the electrolyte is small, and the liquid retention capacity of the separator in the corner area becomes poor.
[0021] In a third aspect, the present application provides a battery module, which includes the lithium-ion battery of the second aspect of the present application.
[0022] In a fourth aspect, the present application provides a battery pack, which includes the lithium-ion battery of the second aspect of the present application or the battery module of the third aspect of the present application.
[0023] In a fifth aspect, the present application provides an electrical device, which includes the lithium-ion battery of the second aspect of the present application or the battery module of the third aspect of the present application or the battery pack of the fourth aspect of the present application; wherein the lithium-ion battery or the battery module or the battery pack is used as a power source or energy storage unit of the electrical device.
[0024] The lithium-ion battery, battery module, battery pack and electrical device of the present application include the isolation membrane of the first aspect of the present application, and thus have at least the same or similar technical effects as the above-mentioned lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1is a front view of a battery cell according to a specific embodiment of the present application;
[0026] Figure 2 is a side view of a battery cell according to a specific embodiment of the present application;
[0027] Figure 3 is a schematic diagram of a layered structure of a non-corner region of an isolation film according to a specific embodiment of the present application;
[0028] Figure 4 is a schematic diagram of a layered structure of a corner region of an isolation membrane according to a specific embodiment of the present application;
[0029] Figure 5 is a schematic diagram of a corner area of an isolation membrane according to a specific embodiment of the present application;
[0030] Figure 6 is a schematic diagram of a corner area of an isolation membrane according to a specific embodiment of the present application;
[0031] Figure 7 is a schematic diagram of a corner area of an isolation membrane according to a specific embodiment of the present application;
[0032] Figure 8 is a schematic diagram of a corner area of an isolation membrane according to a specific embodiment of the present application;
[0033] Fig. 9 is a three-dimensional diagram of a lithium-ion battery according to a specific embodiment of the present application;
[0034] Fig.10 yes Fig. 9 An exploded view of the lithium-ion battery shown;
[0035] Fig.11 is a three-dimensional diagram of a battery module according to a specific embodiment of the present application;
[0036] Fig.12 is a three-dimensional diagram of a battery pack according to a specific embodiment of the present application;
[0037] Fig.13 yes Fig.12 An exploded view of the battery pack shown;
[0038] Fig.14 It is a schematic diagram of an electrical device according to a specific embodiment of the present application.
[0039] The reference numerals are described as follows:
[0040] 1 battery pack,
[0041] 2 upper box,
[0042] 3 lower box,
[0043] 4 battery modules,
[0044] 5. Secondary batteries,
[0045] 51 housing,
[0046] 52 electrode assembly,
[0047] 53 Top cover assembly,
[0048] 54S1 Isolation film non-corner area,
[0049] 54S2 Isolation membrane corner area,
[0050] 541 porous substrate,
[0051] 542 First coating,
[0052] 543 Second coating,
[0053] 544 Third coating. DETAILED DESCRIPTION
[0054] The present application is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0055] Battery separator
[0056] The first aspect of the present application provides a battery isolation membrane, comprising: a porous substrate; a first coating, the first coating is arranged on at least one surface of the porous substrate, the first coating comprises inorganic particles and a binder; a second coating, the second coating is arranged on at least a portion of the surface of the first coating, the second coating comprises ceramic fibers; a third coating, the third coating is arranged on at least a portion of the surface of the second coating, the third coating comprises a polymer gel.
[0057] In an embodiment of the present application, the isolation film includes a non-corner region and a corner region. Figure 1 This is a front view of a battery cell according to some embodiments of the present application. Figure 1 The isolation film non-corner region 54S1 is shown; Figure 2 This is a side view of a battery cell according to some embodiments of the present application. Figure 2 Isolation film corner region 54S2 is shown.
[0058] Furthermore, Figure 3 Schematic diagram of the layered structure of the non-corner region of the isolation film is shown. Figure 3As shown, the non-corner region S1 of the isolation membrane includes a porous substrate 541, and a first coating 542 disposed on at least one surface of the porous substrate 541. The first coating 542 can be various conventional coatings on the surface of the isolation membrane in the prior art. For example, the first coating 542 can include inorganic particles and a binder. The first coating 542 can further include other functional components.
[0059] Figure 4 Figure 2 shows a schematic diagram of the layered structure of the corner area of the isolation membrane. Figure 4 As shown, the corner region S2 of the isolation membrane includes a second coating 543 disposed on at least a portion of the surface of the first coating 542 and a third coating 544 disposed on at least a portion of the surface of the second coating 543 on the basis of a porous substrate 541 and a first coating 542 disposed on at least a surface of the porous substrate 541, wherein the second coating 543 includes ceramic fibers and the third coating 544 includes a polymer gel.
[0060] It can be seen that the embodiment of the present application provides an isolation membrane with regional coatings, and a second coating and a third coating are added on the basis of the first coating in the corner area of the isolation membrane. In the second coating, the ceramic fiber has a certain flexibility and elasticity due to its "velvet"-like structure, which can enhance the liquid absorption capacity of the isolation membrane; in the third coating, the polymer gel has a microporous structure, and after absorbing the electrolyte, it swells and generates a lateral force to press against the electrode, which can improve the situation of insufficient electrolyte caused by the difficulty of retaining liquid in the isolation membrane. Therefore, the isolation membrane of the embodiment of the present application can effectively improve the poor wetting of the battery cell due to insufficient or uneven distribution of electrolyte in the corner area, reduce the risk of local lithium precipitation in the battery cell, and improve the cycle life of the battery cell.
[0061] In some embodiments of the present application, the second coating and the third coating may also be added to the surface of the first coating in the non-corner area of the isolation membrane to improve the poor wetting caused by insufficient or uneven distribution of electrolyte in any local area of the battery cell.
[0062] In some embodiments of the present application, the second coating layer may cover the entire surface of the first coating layer, or may cover a portion of the surface of the first coating layer.
[0063] In some embodiments of the present application, the second coating may be provided in one or more areas. When the second coating is provided in multiple areas, the multiple second coating areas are spaced and distributed on at least a portion of the surface of the first coating; alternatively, the multiple second coating areas are evenly spaced and distributed on at least a portion of the surface of the first coating.
[0064] In some embodiments of the present application, the third coating is provided in one or more areas. When the third coating is provided in multiple areas, the multiple third coatings are spaced and distributed on at least a portion of the surface of the second coating; optionally, the multiple third coatings are spaced and distributed evenly on at least a portion of the surface of the second coating.
[0065] Multiple second coating layers and third coating layers distributed at intervals can more effectively solve the problem of insufficient or uneven distribution of electrolyte in local areas of the isolation membrane, while also controlling the weight and cost of the battery cell and improving the energy density of the battery.
[0066] Figures 5 to 8 It is a schematic diagram of a corner area of an isolation membrane according to some specific embodiments of the present application.
[0067] Figure 5 In the figure, the second coating 543 covers the entire surface of the first coating (not shown), the third coating 544 covers a portion of the surface of the second coating 543, and the second coating 543 and the third coating 544 are both set in one area.
[0068] Figure 6 In the embodiment, the second coating 543 covers a portion of the surface of the first coating 542, and the third coating 544 covers a portion of the surface of the second coating 543, and the second coating 543 and the third coating 544 are both set in one area.
[0069] Figure 7 In the figure, the second coating 543 covers the entire surface of the first coating (not shown in the figure), the third coating 544 is set in multiple areas, and the multiple third coatings 544 are evenly spaced and cover part of the surface of the second coating 543.
[0070] Figure 8 In the embodiment, the second coating layers 543 are disposed in areas spaced apart on a portion of the surface of the first coating layer 542 , and the third coating layer 544 covers a portion of the surface of the second coating layer 543 .
[0071] It should be noted that Figures 5 to 8 What is shown are only several examples of the corner area of the isolation membrane according to the embodiment of the present application. However, the shapes of the first coating, the second coating, and the third coating can be arbitrary, and the setting positions of the first coating, the second coating, and the third coating are not limited thereto.
[0072] In addition, the materials of the first coating, the second coating, and the third coating can be synthesized according to existing literature methods or purchased through commercial channels. The first coating, the second coating, and the third coating can be prepared by methods well known to those skilled in the art such as spraying, photolithography, and printing.
[0073] In some embodiments of the present application, the ceramic fiber is selected from at least one of alumina ceramic fiber, silicon oxide ceramic fiber, silicon nitride ceramic fiber, barium titanate ceramic fiber, titanium oxide ceramic fiber, and magnesium oxide ceramic fiber. Among them, alumina ceramic fiber or silicon oxide ceramic fiber is cheap and light, and can maximize the energy density of the battery while ensuring that the ceramic fiber has a liquid absorption effect.
[0074] In some embodiments of the present application, the thickness of the second coating is 4 μm to 6 μm. In another embodiment of the present application, the thickness of the second coating is 5 μm to 5.5 μm. If the second coating is too thick, the battery energy density will be low and the battery impedance will increase; if the second coating is too thin, the "villi" structure will have low elasticity and will not have a certain liquid absorption effect.
[0075] In some embodiments of the present application, the polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate, polystyrene, polyacrylonitrile, polymethyl acrylate, polyether and fluorine-containing polymer. The polymer gel layer not only plays a role in retaining liquid, but also has the characteristics of good heat insulation, good corrosion resistance and good thermal stability.
[0076] In another embodiment of the present application, the polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate and polystyrene. Among them, polyimide not only has good mechanical properties and heat resistance, but also has good electrolyte wetting properties, which can enable the isolation membrane to have a high electrolyte retention capacity while maintaining strong structural stability. Polyethylene terephthalate has excellent electrical insulation, good electrical properties, fatigue resistance, friction resistance and dimensional stability. Polystyrene is easy to process and shape, inexpensive, and has good thermal insulation, insulation and corrosion resistance.
[0077] In some embodiments of the present application, the thickness of the third coating layer is 3 μm to 5 μm; in another embodiment of the present application, the thickness of the third coating layer is 4 μm to 4.5 μm. If the third coating layer is too thick, it will not only reduce the energy density of the battery, but also increase the resistance of the electrolyte passing through the coating layer, and the electrolyte cannot well infiltrate the entire isolation membrane; and when the third coating layer is too thin, it will affect the liquid retention ability of the gel and fail to achieve a better liquid retention effect.
[0078] In some embodiments of the present application, the particle size of the polymer gel particles in the third coating layer is 100nm to 1000nm; in another embodiment of the present application, the particle size of the polymer gel particles in the third coating layer is 300nm to 500nm. If the particle size of the polymer gel particles is too small, the impedance of the isolation membrane will increase, and it will be more difficult for lithium ions to pass through the isolation membrane, and the transmission speed will be reduced; while if the particle size of the polymer gel particles is too large, the adsorption capacity of the isolation membrane to the electrolyte will be reduced, affecting the liquid retention effect.
[0079] In some embodiments of the present application, the polymer gel particles in the third coating are solid particles or hollow particles. When the polymer gel particles are hollow particles, the third coating can produce a more complete swelling effect after absorbing the electrolyte, which can more effectively improve the situation of insufficient electrolyte caused by the difficulty of retaining liquid in the isolation membrane.
[0080] In some embodiments of the present application, the inorganic particles in the first coating layer include at least one of the following inorganic particles: silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide and tin oxide.
[0081] In some embodiments of the present application, the binder in the first coating includes at least one of the following adhesives: styrene, acrylate, vinyl acetate, fatty acid vinyl ester, epoxy resin, linear polyester, polyvinylidene fluoride, polystyrene, polysulfide rubber, polyacrylic acid, polyacrylate, polyurethane, polyisobutylene, polyvinyl alcohol, polyimide, polyacrylonitrile, polyethylene oxide, polyvinyl pyrrolidone, styrene-butadiene rubber and gelatin.
[0082] Lithium-ion battery
[0083] In a second aspect, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the separator is the separator according to the first aspect of the present application.
[0084] In some embodiments of the present application, the lithium-ion battery includes a wound electrode assembly, and the second coating is arranged on at least a portion of the surface of the first coating in the corner area of the isolation membrane, thereby effectively improving the poor wetting of the battery cell in the corner area due to insufficient or uneven distribution of electrolyte, reducing the risk of local lithium precipitation in the battery cell, slowing down the capacity decay, and improving the cycle life and safety performance of the battery cell.
[0085] In some embodiments of the present application, a plurality of second coatings are arranged at intervals on a portion of the surface of the first coating, and the total area of the arrangement area of the plurality of second coatings accounts for 88% to 95% of the area of the corner area of the separator; in another embodiment of the present application, the total area of the plurality of second coatings accounts for 90% to 92% of the area of the corner area of the separator. In these embodiments, the second coating and the third coating have the same shape and size, and are sequentially stacked on the surface of the first coating. When the total area of the arrangement area of the second coating accounts for too large a proportion of the area of the corner area of the separator, the resistance of lithium ions passing through the separator will increase, the transmission rate will decrease, the electrolyte infiltration effect of the separator will not reach the best, and the impedance of the entire lithium battery will also increase; when the total area of the arrangement area of the second coating accounts for too small a proportion of the area of the corner area of the separator, the ceramic fiber "villi" structure is less, the liquid absorption capacity of the separator in the corner area cannot be significantly improved, and at the same time, the lateral force generated by the swelling of the polymer gel after absorbing the electrolyte is small, and the liquid retention capacity of the separator in the corner area is poor.
[0086] In some embodiments of the present application, the positive electrode plate of the lithium-ion battery includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. In the positive electrode plate, the positive electrode active material layer can be disposed on one surface of the positive electrode current collector or on both surfaces of the positive electrode current collector.
[0087] Those skilled in the art may select a suitable method to prepare the positive electrode sheet, for example, the method may include the following steps: mixing the positive electrode active material, the binder, and the conductive agent to form a slurry, and then coating the slurry on the positive electrode current collector.
[0088] Among them, there is no particular restriction on the specific type of positive electrode active material, as long as it can meet the requirements of embedding and extracting lithium ions. The positive electrode active material can be a layered structure material that allows lithium ions to diffuse in a two-dimensional space, or a spinel structure that allows lithium ions to diffuse in a three-dimensional space. Optionally, the positive electrode active material can be selected from one or more of lithium transition metal oxides, lithium transition metal oxides, and compounds obtained by adding other transition metals or non-transition metals or non-metals. Specifically, the positive electrode active material can be preferably selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates containing olivine structure.
[0089] Among them, the general formula of the lithium-containing phosphate with olivine structure can be LiFe 1-x-y Mn x M' yPO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M' is selected from one or more of other transition metal elements or non-transition metal elements except Fe and Mn, and M' can be selected from one or more of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr. More optionally, the lithium-containing phosphate with olivine structure is selected from one or more of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0090] Lithium transition metal oxide selected from LiCoO2, LiMnO2, LiNiO2, LiMn2O4, LiNi x Co y Mn 1-x-y O2、LiNi x Co y Al 1-x-y O2、LiNi x Mn 2-x O4, wherein 0<x<1, 0<y<1, 0<x+y<1. Optionally, the lithium transition metal oxide is selected from LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.5 Mn 1.5 One or more of O4, LiMn2O4.
[0091] In the positive electrode sheet, the positive electrode active material layer may also include a conductive agent and a binder, wherein the type and content of the conductive agent and the binder are not specifically limited and can be selected according to actual needs. The binder generally includes a fluorinated polyolefin binder. Relative to the fluorinated polyolefin binder, water is generally a good solvent, that is, the fluorinated polyolefin binder generally has good solubility in water. For example, the fluorinated polyolefin binder may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives. In the positive electrode material layer, the mass percentage content of the binder may be due to the poor conductivity of the binder itself, so the amount of the binder cannot be too high. Optionally, the mass percentage content of the binder in the positive electrode active material layer is less than or equal to 2wt% to obtain a lower pole sheet impedance. The conductive agent of the positive electrode sheet may be a variety of conductive agents suitable for secondary batteries in the art, for example, may be a combination of one or more including but not limited to acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black, etc. The weight of the conductive agent may account for 1 wt% to 10 wt% of the total weight of the positive electrode material layer. More optionally, the weight ratio of the conductive agent to the positive electrode active material in the positive electrode sheet is greater than or equal to 1.5:95.5.
[0092] In the positive electrode sheet, the type of positive electrode current collector is not specifically limited and can be selected according to actual needs. The positive electrode current collector can usually be a layer body, and the positive electrode current collector is usually a structure or part that can collect current. The positive electrode current collector can be various materials in the art that are suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to nickel foil and aluminum foil.
[0093] In some embodiments of the present application, the negative electrode plate of the lithium ion battery generally includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material can be a variety of materials suitable for negative electrode active materials of lithium ion batteries in the art, for example, it can be a combination of one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys.
[0094] The negative electrode current collector is generally a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium-ion batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil. In addition, the negative electrode plate can also be a lithium plate.
[0095] In some embodiments of the present application, the electrolyte of the lithium-ion battery can be various electrolytes suitable for lithium-ion batteries in the art, for example, the electrolyte generally includes an electrolyte and a solvent, the electrolyte generally includes a lithium salt, more specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, specifically including but not limited to LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), LiBF2C2O4 (abbreviated as LiDFOB) in one or more combinations. For another example, the concentration of the electrolyte can be 0.8mol / L to 1.5mol / L. The solvent may be any solvent suitable for an electrolyte of a lithium ion secondary battery in the art. The solvent of the electrolyte is usually a non-aqueous solvent and may be an organic solvent, specifically including but not limited to ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate or a combination of one or more of their halogenated derivatives.
[0096] In some embodiments of the present application, the method for preparing the lithium-ion battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet can each be a layer, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery.
[0097] Fig. 9 shows a three-dimensional view of a lithium-ion battery according to a specific embodiment of the present application, Fig.10 yes Fig. 9 Exploded view of a lithium-ion battery is shown. Fig. 9 and Fig.10 According to the present application, the lithium-ion battery 5 (hereinafter referred to as the battery cell 5) includes an outer package 51, an electrode assembly 52, a top cover assembly 53 and an electrolyte (not shown). The electrode assembly 52 is accommodated in the housing 51, and the number of the electrode assembly 52 is not limited, and can be one or more.
[0098] It should be noted that Fig. 9The battery cell 5 shown is a can-type battery, but the present application is not limited thereto. The battery cell 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is eliminated.
[0099] Battery Module
[0100] The third aspect of the present application provides a battery module, which includes the lithium-ion battery described in the second aspect of the present application. In some embodiments, the lithium-ion battery can be assembled into a battery module, and the number of lithium-ion batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Fig.11 4 is a perspective view of a battery module 4 as an example. Fig.11 In the battery module 4, the plurality of lithium-ion batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of lithium-ion batteries 5 may further be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a storage space, and the plurality of lithium-ion batteries 5 are stored in the storage space.
[0101] Battery Pack
[0102] The fourth aspect of the present application provides a battery pack, which includes the battery module described in the third aspect of the present application. In some embodiments, the battery modules can be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Fig.12 is a three-dimensional diagram of a battery pack 1 as an example, Fig.13 yes Fig.12 Exploded view of the battery pack shown. Fig.12 and Fig.13 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0103] Electrical devices
[0104] The fifth aspect of the present application provides an electrical device, which includes the lithium-ion battery described in the second aspect of the present application or the battery module described in the third aspect of the present application or the battery pack described in the fourth aspect of the present application. The lithium-ion battery, the battery module, or the battery pack can be used as a power source for the electrical device or an energy storage unit for the electrical device. The electrical device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0105] The electrical device may select a lithium-ion battery, a battery module or a battery pack according to its usage requirements.
[0106] Fig.14 A schematic diagram of an electric device according to a specific embodiment of the present application is shown. The electric device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module may be used.
[0107] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be light and thin, and the lithium-ion battery of the present application may be used as a power source.
[0108] Those skilled in the art will appreciate that the various limitations or optional ranges for component selection, component content, and material physicochemical performance parameters in the electrochemically active materials in the different embodiments of the present application mentioned above can be combined arbitrarily, and the various embodiments obtained by combining them are still within the scope of the present application and are deemed to be part of the disclosure of this specification.
[0109] Unless otherwise specified, the various parameters involved in this specification have common meanings known in the art and can be measured by methods known in the art. For example, the method provided in the embodiments of the present application can be used for testing. In addition, the optional ranges and options of the various parameters provided in the various optional embodiments can be combined arbitrarily, and the various combinations obtained are considered to be within the scope of the disclosure of the present application.
[0110] The advantages of the present application are further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0111] Preparation of isolation membrane
[0112] 1. Take a 7 μm base film commonly used in the art, apply a first coating on its surface by a conventional method, and the thickness of the first coating is also conventionally selected, for example, 2 μm;
[0113] 2. Mix ceramic fiber, polyvinylidene fluoride, styrene-butadiene rubber (SBR), and water in a mass ratio of 40:1:9:50 to obtain ceramic fiber slurry;
[0114] 3. Mix and disperse the polymer gel, water, and polyvinylidene fluoride in a mass ratio of 35:60:5 to obtain a polymer gel slurry;
[0115] 4. The ceramic fiber is coated on the surface of the first coating by gravure coating, and then dried in an oven at 40-50°C;
[0116] 5. The polymer gel is coated on the surface of the ceramic fiber by rotary spraying, and then dried in an oven at 50-60° C. to finally obtain the isolation membrane described in the present application.
[0117] Preparation of lithium-ion batteries
[0118] 1. Preparation of positive electrode sheet
[0119] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.2:2.7:1.1 to obtain positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.
[0120] 2. Preparation of negative electrode sheet
[0121] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.
[0122] 3. Isolation film
[0123] The isolation membrane adopts the isolation membrane prepared in the examples and comparative examples of the present application.
[0124] 4. Preparation of electrolyte
[0125] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried electrolyte salt LiPF6 is dissolved in the mixed solvent, the concentration of the electrolyte salt is 1.0 mol / L, and the mixture is evenly mixed to obtain an electrolyte solution.
[0126] 5. Preparation of lithium-ion batteries
[0127] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried lithium-ion battery. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0128] The isolation membranes and lithium ion batteries of Examples 1 to 22 and Comparative Examples 1 to 12 were prepared according to the above method.
[0129] Battery performance test
[0130] 1. Capacity and capacity retention rate after 1500 cycles:
[0131] Cyclic performance test: 25℃, 1C / 1C, 1500 cycles.
[0132]
[0133] 2. Lithium analysis of battery cells:
[0134] The tested battery was disassembled to observe the lithium deposition at the interface. The lithium deposition degree was divided according to the lithium deposition at the corners to evaluate the improvement effect of the isolation film described in this application on the lithium deposition at the corners of the battery cell. The basis for division is the percentage of the area of lithium deposition at the corner to the area of the corner region (A).
[0135]
[0136] According to the lithium precipitation situation, the lithium precipitation degree is divided into the following table (lithium precipitation degree: Ⅰ<Ⅱ<Ⅲ<Ⅳ),
[0137] Table 1 Lithium precipitation degree classification table
[0138] Lithium deposition area ratio Lithium precipitation degree classification A<0.3% Ⅰ 0.3%≤A<1% Ⅱ 1%≤A≤3% Ⅲ A≥3% Ⅳ
[0139] Parameters and test results of embodiments and comparative examples
[0140] The parameters and performance test data of Examples 1 to 30 and Comparative Examples 1 to 4 are shown in Table 2.
[0141] Table 2 Parameters and performance test data of the embodiments and comparative examples
[0142]
[0143] Examples 1 to 6 show the effect of the thickness of the second coating on the technical effect. The thickness of the second coating can be 4 μm to 6 μm; optionally, the thickness of the second coating is 5 μm to 5.5 μm. When the thickness of the second coating exceeds 6 μm, the battery energy density may be low and the battery impedance may increase; when the thickness of the second coating is less than 4 μm, the "villi" structure has low elasticity and does not have a good liquid absorption effect.
[0144] Examples 3, 7-10 show examples where the third coating includes different types of polymer gels. Applying polymer gels such as polyimide, polyethylene terephthalate, polystyrene, polyacrylonitrile, and polymethyl acrylate to the third coating can achieve better technical effects. The battery capacity and capacity retention rate are at a high level after 1,500 cycles, and lithium precipitation is not easy to occur. Among them, polyimide not only has good mechanical properties and heat resistance, but also has good electrolyte wetting properties, which can enable the isolation membrane to have a high electrolyte retention capacity while maintaining strong structural stability, making it a better choice.
[0145] Examples 3, 11-15 show the effect of the thickness of the third coating on the technical effect. The thickness of the third coating can be 3μm to 5μm, and optionally, the thickness of the third coating can be 4μm to 4.5μm. When the thickness of the third coating exceeds 5μm, the battery energy density may be reduced, and the resistance of the electrolyte passing through the coating increases, and the electrolyte cannot well infiltrate the entire isolation membrane. When the thickness of the third coating is less than 3μm, the liquid retention capacity of the gel is affected, and a better liquid retention effect cannot be achieved.
[0146] Examples 3, 16-20 show the effect of the particle size of the polymer gel particles in the third coating on the technical effect. The particle size of the polymer gel particles in the third coating can be 100nm to 1000nm; optionally, the particle size of the polymer gel particles in the third coating is 300nm to 500nm. If the particle size of the polymer gel particles is less than 100nm, the impedance of the isolation membrane will increase, and lithium ions will have certain difficulties passing through the isolation membrane, and the transmission speed will be reduced; and if the particle size of the polymer gel particles is greater than 1000nm, the adsorption capacity of the isolation membrane to the electrolyte will be reduced, which will have a certain adverse effect on the liquid retention effect.
[0147] Examples 3 and 21 show the influence of hollow / solid gel particles on the technical effect. When the polymer gel particles are hollow particles, the swelling effect of the polymer gel layer after absorbing the electrolyte is more significant, which can more effectively improve the situation of insufficient electrolyte caused by the difficulty of retaining liquid in the isolation membrane.
[0148] Examples 3, 22-26 show the influence of the proportion of the total area of the second coating layer relative to the area of the corner region of the isolation membrane on the technical effect. The total area of the area where the second coating layer is set can account for 88% to 95% of the area of the corner region of the isolation membrane. Optionally, the total area of multiple second coating layers can account for 90% to 92% of the area of the corner region of the isolation membrane. When the total area of the second coating layer accounts for more than 95% of the area of the corner region of the isolation membrane, the resistance of lithium ions passing through the isolation membrane increases, the transmission rate decreases, the electrolyte infiltration effect of the isolation membrane cannot reach the best, and the impedance of the entire lithium battery will also increase; when the total area of the second coating layer accounts for less than 88% of the area of the corner region of the isolation membrane, the "villi" structure of the ceramic fiber is less, and the liquid absorption capacity of the isolation membrane in the corner region cannot be significantly improved. At the same time, the lateral force generated by the swelling of the polymer gel after absorbing the electrolyte is small, and the liquid retention capacity of the isolation membrane in the corner region is deteriorated.
[0149] Examples 3 and 27 show the influence of the distribution of the additional second coating layer and the third coating layer on the technical effect. Multiple second coating layers and third coating layers distributed at intervals can more effectively solve the problem of insufficient or uneven distribution of electrolyte, while controlling the weight and cost of the battery cell and improving the energy density of the battery.
[0150] Examples 28-30 show some other different types of ceramic fibers and polymer gels as materials for the second coating and the third coating, which can be applied to the examples in the embodiments of the present application and can achieve the technical effects of the present invention.
[0151] The surface of the corner area of the isolation membrane of Comparative Example 1 is only provided with the first coating; the surface of the corner area of the isolation membrane of Comparative Example 2 is only provided with the first coating and the second coating; the surface of the corner area of the isolation membrane of Comparative Example 3 is only provided with the first coating and the third coating; the difference between Comparative Example 4 and Example 3 is that the positions of the second coating and the third coating are interchanged. The cycle performance and capacity retention rate of Comparative Examples 1-4 are obviously insufficient compared with the examples, and the lithium precipitation is aggravated. From the comparison of the data of the comparative examples and the examples, it can be seen that the isolation membrane provided by the present invention can effectively improve the poor wetting of the battery cell caused by insufficient or uneven distribution of electrolyte in the corner area, reduce the risk of local lithium precipitation of the battery cell, improve the energy density of the battery, and extend the cycle life of the battery cell.
[0152] According to the disclosure and teaching of the above description, those skilled in the art may also make changes and modifications to the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and some modifications and changes to the present application should also fall within the scope of protection of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.
Claims
1. A separation film, characterized in that: include: Porous substrates; A first coating layer, the first coating layer is disposed on at least one surface of the porous substrate, the first coating layer comprising inorganic particles and a binder; a second coating layer, the second coating layer being disposed on at least a portion of the surface of the first coating layer, the second coating layer comprising ceramic fibers; The third coating layer is disposed on at least a portion of the surface of the second coating layer, and the third coating layer comprises a polymer gel.
2. The isolation film according to claim 1, characterized in that: The second coating layer is disposed in one or more areas, and the plurality of second coating layers are distributed at intervals on at least a portion of the surface of the first coating layer; and / or, The third coating layer is disposed in one or more areas, and the plurality of third coating layers are distributed at intervals on at least a portion of the surface of the second coating layer.
3. The isolation film according to claim 1, characterized in that: The ceramic fiber is selected from at least one of alumina ceramic fiber, silicon oxide ceramic fiber, silicon nitride ceramic fiber, barium titanate ceramic fiber, titanium oxide ceramic fiber and magnesium oxide ceramic fiber.
4. The isolation film according to claim 1, characterized in that: The thickness of the second coating layer is 4 μm to 6 μm.
5. The isolation film according to claim 4, characterized in that: The thickness of the second coating layer is 5 μm to 5.5 μm.
6. The isolation film according to claim 1, characterized in that: The polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate, polystyrene, polyacrylonitrile, polymethyl acrylate, polyether and fluorine-containing polymer.
7. The isolation film according to claim 6, characterized in that: The polymer gel is selected from at least one of the following types of polymer gels: polyimide, polyethylene terephthalate, and polystyrene.
8. The isolation film according to claim 1, characterized in that: The thickness of the third coating layer is 3 μm to 5 μm.
9. The isolation film according to claim 8, characterized in that: The thickness of the third coating layer is 4 μm to 4.5 μm.
10. The isolation film according to claim 1, characterized in that: The particle size of the polymer gel in the third coating layer is 100nm-1000nm.
11. The isolation film according to claim 10, characterized in that: The particle size of the polymer gel in the third coating layer is 300nm-500nm.
12. The isolation film according to claim 1, characterized in that: The polymer gel particles in the third coating layer are solid particles or hollow particles.
13. The isolation film according to claim 1, characterized in that: The inorganic particles in the first coating layer include at least one of the following inorganic particles: silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide and tin oxide; The binder in the first coating includes at least one of the following adhesives: styrene, acrylate, vinyl acetate, fatty acid vinyl ester, epoxy resin, linear polyester, polyvinylidene fluoride, polystyrene, polysulfide rubber, polyacrylic acid, polyacrylate, polyurethane, polyisobutylene, polyvinyl alcohol, polyimide, polyacrylonitrile, polyethylene oxide, polyvinyl pyrrolidone, styrene-butadiene rubber and gelatin.
14. A lithium ion battery comprising: Positive electrode sheet, negative electrode sheet, separator between the positive electrode sheet and the negative electrode sheet, and electrolyte, Wherein, the isolation membrane is the isolation membrane according to any one of claims 1 to 13.
15. The lithium ion battery according to claim 14, characterized in that: The lithium-ion battery includes a wound electrode assembly, and the second coating layer is disposed at least on a portion of the surface of the first coating layer in a corner region of the separator.
16. The lithium ion battery according to claim 15, characterized in that: A plurality of the second coating layers are disposed at intervals on a portion of the surface of the first coating layer, The total area of the plurality of second coating layers accounts for 88% to 95% of the area of the corner region of the isolation film.
17. The lithium ion battery according to claim 16, characterized in that: The total area of the plurality of second coating layers accounts for 90% to 92% of the area of the corner region of the isolation film.
18. A battery module, characterized in that: Comprising a lithium ion battery according to any one of claims 14-17.
19. A battery pack, characterized in that: It comprises a lithium-ion battery according to any one of claims 14 to 17 or a battery module according to claim 18.
20. An electrical device, characterized in that: It comprises a lithium-ion battery according to any one of claims 14 to 17, or a battery module according to claim 18, or a battery pack according to claim 19, wherein the lithium-ion battery, the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.
Citation Information
Patent Citations
Improved battery separators and related methods
CN108140787A
Coating diaphragm with improved structure and preparation method thereof
CN111244374A